Women in Adébáyọ̀ Fálétí’s Poetry - Abidemi Bolarinwa (Yoruba Studies Review)
Women have been victims of gender ideology which, according to Hussein (2005), is a systemic set of cultural beliefs through which a society constructs and wields its gender relations and practices. Gender ideology contains legends, narratives and myths about what it means to be a man or a woman and suggests how each should behave in a society (Olabode, 2009). Women are a non-homogenous group as their status and roles in the society are determined by a complexity of factors such as being a daughter, sister, and wife; a cultic member; and the economic and political positions they hold in the market place and in local governance (Ilesanmi, 2013). Sub-ethnic variations were also reported in customs and practices such as a marriage and family life, pre-natal and post-natal practices and others. Men in various sub-ethnic (Yorùba) groups are given privileges in matters relating to power and control ́ in domestic and public spheres. Since culture is not static but rather dynamic, therefore contemporary writers are now advocating for portrayal that will extol women’s virtues, thereby bringing to the fore the indispensable roles women play in society. In order to redeem and recreate an enhanced status for women, studies about women abound in literary studies, with little attention given to issues of women in Adébayó ̀ Fa ̩ ́letí ’s poetry. Thus, using the feminist approach ex ́ - amines how women are portrayed in Fálétí’s poetry so as to establish his view about the womenfolk.